EVALUASI PROGRAM PENDIDIKAN INKLUSIF DI SEKOLAH DASAR CINUNUK 01 MENGGUNAKAN MODEL CIPP (CONTEXT, INPUT, PROCESS, PRODUCT) - Nabila Tri; Mila Deskia (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2024)
Inclusive education at SDN Cinunuk 01 faces the main challenge of the lack of special services and adequate support, including accompanying teachers and infrastructure. The purpose of this program is to ensure equal access to education for all students, including ABK. This qualitative descriptive research evaluates the effectiveness of the program through questionnaires, observations, and interviews, analyzing how effectively schools meet inclusion goals. Evaluation includes four aspects. The Context aspect examines the social conditions of students, special needs, and support for inclusion policies at the regional and national levels. Input focuses on school resources: facilities, teacher quality, and ABK special teaching materials. Process assesses the implementation of inclusive curriculum, teaching methods, and the involvement of parents and the community. Finally, Product measures academic achievement, participation in school activities, and socio-emotional development of ABK. The findings from these four aspects are expected to provide insight to formulate more effective and responsive education policies. Data will be the basis for schools and stakeholders to improve the quality of inclusive education services, including better provision of resources, teacher training, and more adaptive curriculum development. This research aims to increase awareness and active participation of parents and the community, create a better learning environment for all students, and develop an inclusive education model that can be adopted by other schools.